Gender Bias and Empowering Women in Short Film “Padanan”: Bias Gender dan Pemberdayaan Perempuan dalam Film Pendek “Padanan” - Raihana, Yasmin; Fikri, M. Andi (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to identify, explain, and analyze different behaviors towards genders. The short film